Using Game Based Learning to Optimize 4C Skills in Elementary/MI - Afifah Andari, Dyah; Mukarromah, Aenullael (Alifbata : Jurnal Pendidikan Dasar, 2026)
Twenty first century education requires students to possess key competencies known as the 4C skills (Critical Thinking, Communication, Collaboration, and Creativity). The Merdeka Curriculum at the elementary schools level encourages the implementation of innovative learning models that can foster these four skills. One effective approach is Game-Based Learning (GBL), a game-based instructional method that emphasizes interaction, challenge, and collaboration. This research employs a Systematic Literature Review method using articles and scientific journals published between 2020–2025. Data sources were collected from accredited national journals and reputable international journals discussing GBL and the development of 4C skills in elementary education. The findings indicate that GBL contributes significantly to the improvement of all four 4C skills. Game elements such as challenges, rules, instant feedback, and social interaction have been proven to enhance students’ critical thinking abilities, increase creativity in problem solving, strengthen communication among students, and build teamwork. In addition, GBL also boosts students’ motivation and active participation during the learning process. These findings suggest that GBL is a relevant and effective approach to be applied within the Merdeka Curriculum, particularly in developing essential 21st-century skills at the elementary schools level.